Pengaruh experiential marketing terhadap kepuasan pelanggan Starbucks di Makassar - Bubun, Uli Urbanus; Limpo, Lita; Sampe, Ferdinandus (Relawan Sosial Ekonomi (RSE) Publisher, 2023)
This study aims to examine the effect of experiential marketing on customer satisfaction at Starbucks in Makassar. The experiential marketing dimension can be seen from sense, feel, think, act & relate. The research was conducted on Starbucks customers in Makassar using a non-probability sampling technique. Data were collected using questionnaires. As many as 100 respondents participated in the survey. Data were analysed using using the SPSS version 22.00 to identify respondents charactistic, validity and reliability tests, multiple linear regression analysis and hypothesis testing. From the research results it can be seen that simultaneously experiential marketing consisting of sense, feel, think, act, and relate had a significant influence on Starbucks customer satisfaction. The partial test results show that only three variables, namely sense, feel and relate, significantly influenced Starbucks customer satisfaction. It is suggested that Starbucks Management should innovate to provide more convenience.